Menelisik Kontribusi Ayah dalam Menanamkan Kesabaran pada Anak di Keluarga Kristen - Manurung, Kosma; Walean, Jefrie (Jurnal Salvation, 2023)
Abstract: Patience is important to be taught by fathers to their children because it is very relevant, has an impact on children's social emotional intelligence, and is related to children's success in the future. This article intends to examine the contribution of fathers in instilling patience in children in Christian families. By using the description method and supported by literature review, it is hoped that it can provide a clear, in-depth picture, and have an academic footing related to patience in the Bible description, the importance of patience for children, and the maximum contribution that fathers can make in instilling patience in children. It was concluded that fathers greatly contributed to instilling patience in children when actively involved in educating children, introducing patience as early as possible, understanding this is a long-term effort, a unique form of affection for children, and the closest example that can be imitated by children. Abstrak: Kesabaran penting diajarkan oleh ayah kepada anaknya karena sangat relevan, berdampak pada kecerdasan sosial emosional anak, serta terkait dengan kesuksesan anak dimasa depan. Artikel ini bermaksud menelisik kontribusi ayah dalam menanamkan kesabaran pada anak di keluarga Kristiani. Dengan menggunakan metode deskripsi dan didukung oleh kajian literatur diharapkan dapat memberikan gambaran yang jelas, mendalam, serta memiliki pijakan akademik terkait dengan kesabaran dalam gambaran Alkitab, pentingnya kesabaran bagi anak, dan kontribusi maksimal yang ayah bisa berikan dalam menanamkan kesabaran pada anak. Disimpulkan bahwa ayah sangat berkontribusi dalam menanamkan kesabaran pada anak ketika terlibat aktif mendidik anak, memperkenalkan kesabaran sedini mungkin, memahami ini usaha jangka panjang, bentuk kasih sayang yang unik kepada anak, dan contoh paling dekat yang dapat ditiru oleh anak.